Conservation of triplet-triplet energy transfer photoprotective pathways in fucoxanthin chlorophyll-binding proteins across algal lineages - Agostini, Alessandro; Bína, David; Carbonera, Donatella; Litvín, Radek (Biochimica et biophysica acta. Bioenergetics, 2023)
Detailed information on the photo-generated triplet states of diatom and haptophyte Fucoxanthin Chlorophyll-binding Proteins (FCPs and E-FCPs, respectively) have been obtained from a combined spectroscopic investigation involving Transient Absorption and Time-Resolved Electron Paramagnetic Resonance. Pennate diatom Phaeodactylum tricornutum FCP shows identical photoprotective Triplet-Triplet Energy Transfer (TTET) pathways to the previously investigated centric diatom Cyclotella meneghiniana FCP, with the same two chlorophyll a-fucoxanthin pairs that involve the fucoxanthins in sites Fx301 and Fx302 contributing to TTET in both diatom groups. In the case of the haptophyte Emilianina huxleyi E-FCP, only one of the two chlorophyll a-fucoxanthins pairs observed in diatoms, the one involving chlorophyll a409 and Fx301, has been shown to be active in TTET. Furthermore, despite the marked change in the pigment content of E-FCP with growth light intensity, the TTET pathway is not affected. Thus, our comparative investigation of FCPs revealed a photoprotective TTET pathway shared within these classes involving the fucoxanthin in site Fx301, a site exposed to the exterior of the antenna monomer that has no equivalent in Light-Harvesting Complexes from the green lineage.
Keywords: rozsivky; Diatom; Electron Spin Resonance Spectroscopy; proteiny vázající chlorofyl; Chlorophyll A; Chlorophyll Binding Proteins; chlorofyl; Energy Transfer; TR-EPR; Diatoms; Emiliania huxleyi; Carotenoid; Photoprotection; chlorofyl a; Chlorophyll; Light-harvesting complex; přenos energie; elektronová paramagnetická rezonance